Visible and invisible risks: Exploring washing and hygiene practices with women living on low income in Kenya - Robinson, J.; Howland, Olivia (Informa UK Limited, 2022)
Shifting environmental conditions and poor or insufficient hygiene facilitates the transmission of bacteria and viruses between and within species of animals; between humans; and between humans and animals. Taking a One Health perspective, we used interviews to explore with 20 women living on low income in Kenya: their gendered hygiene practices and daily contact with animals; how and why they access water and sanitation facilities for themselves, their families, and any livestock; and their understandings of (zoonotic) health risks and disease transmission within their local environments. The women described how they worked every day to keep bodies and homes clean by washing bodies, surfaces and clothes. Women's hygiene practices focussed on removing visible dirt partly because of concerns for health but also to support their families’ social standing in their community. While they were less aware of any ‘invisible’ risks to health through contact with animals or other hazards present in their daily living environments, most exercised care to source and manage water for drinking. Contaminated water was recognised as a risk to health suggesting that in this case, women accepted that there were ‘invisible risks’ to health, even in clear water, and took steps to mitigate them.